SISTEM PENUNJANG KEPUTUSAN PEMILIHAN BEASISWA DENGAN METODE DECISION TRE ID3 PADA SMAN 2 CIBINONG KABUPATEN BOGOR - Linda Sukmawati (JURNAL ILMIAH INFORMATIKA, 2019)
The selection of scholarships must be in accordance with established rules. The criteria set out in this case study are academic values, parents' income, number of siblings, number of dependents of parents, active organizations and others. Therefore not all who register as candidates for the scholarship will be accepted, only those who meet the criteria will get the scholarship. Because of the large number of participants who apply for scholarships, it is necessary to build a decision support system that will help determine who is entitled to get the scholarship. Therefore, this study seeks to provide a solution for the selection of students who deserve a scholarship in accordance with the criteria that have been determined by each to produce more accurate and faster data. Decision Tree ID3 method as a comparative test analysis model, as well as policy analysis is used to support appropriate decision making for the school board. ID3 Decision Tree is suitable for use in this case because it can make data classification accuracy and tree generated results are very easy to read by humans.